Penerapan Model Pembelajaran Snowball Throwing Terhadap Peningkatan Berpikir Kritis Siswa di Wachid Hasyim Surabaya - Maula, Virda Rohmatul; Rahayu, Fitri; Badriyah, Laila (CV Era Digital Nusantara, 2025)
This research aims to evaluate the application of the Snowball Throwing learning model to improve students' critical thinking skills at Wachid Hasyim High School Surabaya. The research method used was an experimental method with a pre-test and post-test design in two groups, namely the experimental group which used the Snowball Throwing learning model and the control group which used conventional methods. Data was collected through critical thinking tests before and after treatment, as well as observing student activities during the learning process. The results showed that there was a significant increase in students' critical thinking abilities in the experimental group compared to the control group. The application of the Snowball Throwing learning model is effective in encouraging active student participation, strengthening conceptual understanding, and improving problem analysis and evaluation skills. These findings suggest that the Snowball Throwing learning model can be used as an alternative learning strategy to improve students' critical thinking skills in the school environment.